Transcatheter treatment of iatrogenic brachiocephalic-jugular arteriovenous fistula and aortopulmonary artery fistula: A case report - Krit Makonkawkeyoon (2018)
Iatrogenic arteriovenous fistula is not a common complication of central venous catheterization. Duct occluder devices have been developed for patent ductus arteriosus occlusions but they may be used for arteriovenous fistula closures. We report a case of iatrogenic brachiocephalic-jugular and aortopulmonary artery fistulas after central venous catheter insertion. The fistulas were successfully managed with duct occluder devices. Due to increasing number of central venous catheterizations, physicians should be aware of this uncommon complication. Transcatheter closing of brachiocephalic-jugular and aortopulmonary artery fistulas by duct occluder devices seems to be a safe and feasible form of treatment. © 2013 Wiley Periodicals, Inc. Copyright © 2013 Wiley Periodicals, Inc.